ANESTHETIC MANAGEMENT FOR ABDOMINAL HYSTERECTOMY IN HEART TRANSPLANT RECIPIENT - Karadjova, Dafina; Mehmedovik, Nadica; Sivevski, Atanas; Aleksioska Papestiev, Irena; Pop-Stefanija, Vesna; Gjorgjevikj, Aleksandra (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2023)
Every year, the number of heart transplants in the world, but also in our country, is increasing. Because of high survival rates and increased life expectancy, heart transplant patients are likely to require elective or emergent non-cardiac surgical procedures. Heart transplant recipients present unique anesthetic challenges due to modified autonomic physiology and modified drug response. We present the perioperative management of 41-years-old woman,with a heart transplant before 30 months, admitted to the hospital for elective abdominal hysterectomy.
Keywords: abdominal hysterectomy; anesthetic management; heart transplant